A high-strength heat-resistant Al−5.7Ni eutectic alloy with spherical Al3Ni nano-particles by selective laser melting. (October 2021) - Deng, Junwang; Chen, Chao; Liu, Xiaochun; Li, Yunping; Zhou, Kechao; Guo, Shengmin
Abstract: Traditional high-strength wrought aluminum alloys are sensitive to cracks in additive manufacturing (AM) while the eutectic aluminum alloys can be reliably printed. To explore a high-strength heat-resistant aluminum alloys by AM, in this paper, we proposed to retard the solidification range by using an Al−5.7Ni alloy, thus alleviate crack formation tendency. The AM parts of this alloy was featured by uniformly distributed spherical Al3 Ni nano-particles with an average size of 33 nm, showing a novel coherent crystallographic relationship with the matrix, <110>Al //<113>Al3Ni and 111Al //211Al3Ni . Excellent mechanical property was achieved in this crack-free alloy with tensile strength of 410 MPa at room temperature and 140 MPa at 300°C, mainly attributed to the dispersion strengthening from the Al3 Ni nano-particles with superior thermal stability. Graphical abstract: Image, graphical abstract